A case study of rupture in overhead ground wire twined by armor rod. (January 2022) - Deng, Honglei; Peng, Ruidong; Zhong, Meishan; Yang, Rui; Liang, Yongchun; Guo, Deming; Liu, Gang
Highlights: A comprehensive analysis method combined with simulation experiment is presented. A FE model of AR terminal based on electromagnetic-thermal coupling is proposed. Based on the FE model, the overheating mechanism at AR terminal is discussed. Discharge is the prime factor that causes the high temperature of OGW in accident. The presence of AR terminal increases the rupture risk of OGW. Abstract: The armor rod (AR) is used to repair the damaged overhead ground wire (OGW) and prevent the wear of the OGW in the suspension clamp in engineering. Once the OGW at the AR terminal breaks, it may lead to temporary blackout, which also causes the severe economic losses, or even threatening public safety. However, there are few literature or report about this type of accident at present. Therefore, based on a rupture accident of OGW at the AR terminal, the reason for this accident was investigated in this paper. Firstly, the description of the accident background and the material analysis for the accident sample were presented to preliminarily determine the damage characteristics of OGW and the cause of the accident. Secondly, simulation experiments for the transient temperature rise of the AR terminal were conducted. The macroscopic morphology characteristics of the experimental samples were also analyzed. Finally, based on the electromagnetic thermal coupling, a finite element model of the AR terminal of OGW was established. The overheating mechanism at the AR terminal was also discussed according to the model. The discharge occurrs at the AR terminal under the short-circuit current (SCC), and it is also the prime factor that causes the high temperature of OGW. The research methods and conclusions in this paper can provide theoretical guidance for the analysis of similar accidents and the optimization design of structures.